PENGARUH MOTIVASI DAN PELATIHAN TERHADAP KINERJA ANGGOTA SATUAN RESERSE KRIMINAL DI POLRES GUNUNGKIDUL (Jurnal Riset Akuntansi dan Bisnis Indonesia, 2022)
This study was conducted to determine and analyze the effect of work motivation and training on the performance of members of the Criminal Investigation Unit at the Gunungkidul Police. This study uses a quantitative approach with questionnaire data collection methods to all members of the Satreskrim Polres Gunungkidul totaling 52 people. Data analysis used multiple linear regression. The results showed that partially and simultaneously motivation and training had a significant effect on the magnitude of the influence of X1 and X2 on y of 82.82%, meaning that the magnitude of the influence of motivation and training in influencing performance was 82.82%. The implications of the results of this research for the Gunungkidul Police continue to carry out work motivation and conduct training to members so that in the future the performance of employees and the performance of the Criminal Investigation Unit at the Gunungkidul Police will be even better.
Keywords: Motivation; training; performance of members; Satreskrim Polres Gunungkidul.